2019
DOI: 10.1111/febs.14871
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan preconditioning of monocytes/macrophages affects their angiogenic behavior and regulation of TSG‐6 expression in a tumor type‐specific manner

Abstract: Hyaluronan is a glycosaminoglycan normally present in the extracellular matrix in most tissues. Hyaluronan is a crucial player in many processes associated with cancer, such as angiogenesis, invasion, and metastasis. However, little has been reported regarding the action of hyaluronan on monocytes/macrophages (Mo/MØ) in tumor angiogenesis and its consequences on tumor development. In the present study, we investigated the effects of hyaluronan of different sizes on human Mo/MØ angiogenic behavior in colorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…Moreover, HA can modulate immune systems, and it is generally accepted that low and high molecular mass HA have pro-and antiinflammatory properties, respectively (11). Further, heavy chains (HC) of inter-alpha-trypsin inhibitor can be covalently bound to HA, forming HC-HA matrices, through the action of tumor necrosis factor-inducible gene 6 protein (TSG6) (12,13). Although HC-HA has an essential physiological role during mammalian oocyte maturation (14), in pathological conditions monocytes interact with HC-HA matrices via cell surface CD44, thereby contributing to immune cells recruitment to the site of inflammation (15).…”
Section: Hyaluronanmentioning
confidence: 99%
“…Moreover, HA can modulate immune systems, and it is generally accepted that low and high molecular mass HA have pro-and antiinflammatory properties, respectively (11). Further, heavy chains (HC) of inter-alpha-trypsin inhibitor can be covalently bound to HA, forming HC-HA matrices, through the action of tumor necrosis factor-inducible gene 6 protein (TSG6) (12,13). Although HC-HA has an essential physiological role during mammalian oocyte maturation (14), in pathological conditions monocytes interact with HC-HA matrices via cell surface CD44, thereby contributing to immune cells recruitment to the site of inflammation (15).…”
Section: Hyaluronanmentioning
confidence: 99%
“…Hyaluronan synthesis and degradation are strictly regulated in physiological conditions, but in the tumoral tissues they are dysregulated, originating HA of different molecular sizes, which in turn have different functions [ 42 ]. Even more, HA interaction with specific binding proteins and receptors modulating its function in tumoral context [ 30 ]. It is well known that members of the family of molecules of the HA signaling pathway, like HA synthases (HAS1, HAS2, HAS3), HA receptors and hyaluronidases (mainly HYAL1) are critical determinants of tumor growth and progression [ 16 , 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result can indicate that in colorectal, but not breast cancer, HA metabolism in the tumor tissue tends to up regulate or down regulate in its entirety, showing the alteration in entire metabolism rather than just one molecule. However, we have previously observed that the effect of HMW HA as an inductor of the angiogenic behavior of macrophages in breast cancer is in part consequence of the presence of TSG-6 [ 30 ]. This observation could indicate that the function of HA, more than its metabolism, could be altered in the case of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer development it is well known that HA expression is usually altered, affecting several mechanisms associated, among others, with cell proliferation and survival, invasion, angiogenesis and multidrug resistance, [19][20][21][22][23][24]. Even more, it has been recently demonstrated that HA also affects immune cells recruitment and in ammation [25]. On the other hand, UGDH has been proposed as a novel candidate biomarker of prostate cancer that may complement the development of a multi-biomarker panel for detecting tumor transformation within the adjacent tumor tissue [26].…”
Section: Introductionmentioning
confidence: 99%